Bistable switch molecule DPACdCl4 showing four physical channels and high phase transition temperature - Zhang, Ying-Yu; Luo, Jia-Qi; Han, Yan; Zhang, Wan-Ying; Zhang, Yi; Lu, Hai-Feng; Fu, Da-Wei (Chinese chemical letters, 2025)
Multiple switchable physical channels within one material or device, encompassing optical, electrical, thermal, and mechanical pathways, can enable multifunctionality in mechanical-thermal-opto-electronic applications. Achieving integrated encryption and enhanced performance in storage and sensing presents a formidable challenge in the synthesis and functionality of new materials. In an effort to overcome the complexities associated with these multiple physical functions, this study investigates the large-size crystal of DPACdCl4 (DPA = diisopropylammonium), revealing significant features in rare multi-channel switches. This compound demonstrates the ability to switch between "OFF/0" and "ON/1" states in the mechanical-thermal-opto-electronic channels. Consequently, DPACdCl4 possesses four switchable physical channels, characterized by a higher phase transition temperature of 440.7 K and a competitive piezoelectric coefficient of 46 pC/N. Furthermore, solid-state NMR analysis indicates that thermally activated molecular vibrations significantly contribute to its multifunctional switching capabilities. The large-size molecular single crystal, processed from aqueous solution, is a multiple switchable materials, which exhibits the optical-electrical-thermal-mechanical switchable physical channels, including nonlinear optical SHG (optical), dielectricity (electrical), pyroelectricity (thermal) and piezoelectricity (mechanical). [Display omitted]